2015
DOI: 10.1007/s10681-015-1526-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and combining ability analysis of slow rusting stem rust resistance and yield and related traits in bread wheat

Abstract: Bread wheat genotypes with slow rusting stem rust resistance were crossed in a half-diallel mating design to identify superior parents for stem rust resistance combined with high grain yield (GY) and related traits. Significant mid-parent heterosis for area under disease progress (AUDPC) was observed in crosses 7041-1 9 Danda'a and Danda'a 9 Kubsa. H04-2 9 Danda'a showed significant mid-parent heterosis for GY, thousand kernel weight (TKW), number of tillers per plant (TPP) and reduced plant height (PLH), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
(25 reference statements)
2
8
0
2
Order By: Relevance
“…Finally, heterosis estimates indicated that, the best crosses over their mid and better parents were Giza168 x Sids12 (P 1 X P 4 ), Giza168 x Sakha94 (P 1 X P 5 ), Giza168 x Gemmeiza10 (P 1 X P 8 ), Misr1 x Sakha94 (P 2 X P 5 ), Sakha93 x Misr2 (P 3 X P 6 ), Sakha94 x Misr2 (P 5 X P 6 ), Sakha94 x Gemmeiza9 (P 5 X P 7 ), Misr2 x Gemmeiza9 (P 6 X P 7 ) and Gemmeiza9 x Gemmeiza10 (P 7 X P 8 ). Similar results also, found by Moshref (2006);El-Borhamy et al, (2008); Mekhamer (2009); Akbar et al, (2010); Kumar et al, (2011); Sulaiman (2011); Hussain et al, (2013); Pankaj Garg et al, (2015); Said Salman et al, (2015); and Hei et al, (2016).…”
Section: Heterosis Effectssupporting
confidence: 76%
“…Finally, heterosis estimates indicated that, the best crosses over their mid and better parents were Giza168 x Sids12 (P 1 X P 4 ), Giza168 x Sakha94 (P 1 X P 5 ), Giza168 x Gemmeiza10 (P 1 X P 8 ), Misr1 x Sakha94 (P 2 X P 5 ), Sakha93 x Misr2 (P 3 X P 6 ), Sakha94 x Misr2 (P 5 X P 6 ), Sakha94 x Gemmeiza9 (P 5 X P 7 ), Misr2 x Gemmeiza9 (P 6 X P 7 ) and Gemmeiza9 x Gemmeiza10 (P 7 X P 8 ). Similar results also, found by Moshref (2006);El-Borhamy et al, (2008); Mekhamer (2009); Akbar et al, (2010); Kumar et al, (2011); Sulaiman (2011); Hussain et al, (2013); Pankaj Garg et al, (2015); Said Salman et al, (2015); and Hei et al, (2016).…”
Section: Heterosis Effectssupporting
confidence: 76%
“…Moreover, the selection of these traits would not be effective in a single condition but more conditions would be required. In this respect, Naseem et al (2015), Abdallah, et al (2015, Hei et al (2016), Kaur and Mondal (2016) , El-Saadoown et al (2017), Jatav et al (2017) Nevertheless, GCA variance values were higher than SCA for all characters under these study at the two sowing dates, proving that, selection for improve the studied characters would be more effective using some of the present parents and crosses. In addition, the ratios of GCA/SCA under the two sowing dates were more than unity for all characters, except for GFP under optimum sowing date, KW under both conditions and GY under late sowing date, meaning that additive gene effects predominantly control these characters.…”
Section: C-combining Ability 1-analysis Of Variancementioning
confidence: 55%
“…Short stature wheat genotypes are mostly preferred because dwarf wheat genotypes have the minimum chances of lodging. In past studies, lines and testers were found with negative GCA and their line by tester populations also revealed negative SCA for plant height in wheat (Hei et al, 2015;attar et al, 2018). Earlier findings revealed that lines were found as excellent parental genotypes for crossing with various testers for plant height and yield-related traits in wheat (Istipliler et al, 2015).…”
Section: Discussionmentioning
confidence: 93%